Real‐world impact of non–breast cancer–specific death on overall survival in resectable breast cancer. Issue 13 (7th March 2017) - Fu, Jianfei; Wu, Lunpo; Jiang, Mengjie; Li, Dan; Jiang, Ting; Fu, Wei; Wang, Liangjing; Du, Jinlin
Abstract : BACKGROUND: The real‐world occurrence rate of non–breast cancer–specific death (non‐BCSD) and its impact on patients with breast cancer are poorly recognized. METHODS: Women with resectable breast cancer from 1990 to 2007 in the Surveillance, Epidemiology, and End Results database (n = 199, 963) were analyzed. The outcome events of breast cancer were classified as breast cancer–specific death (BCSD), non‐BCSD, or survival. Binary logistics was used to estimate the occurrence rates of non‐BCSD and BCSD with different clinicopathological factors. The Gray method was used to measure the cumulative incidence of non‐BCSD and BCSD. The ratio of non‐BCSDs to all causes of death and stacked cumulative incidence function plots were used to present the impact of non‐BCSD on overall survival (OS). Models of Cox proportional hazards regression and competing risk regression were compared to highlight the suitable model. RESULTS: There were 12, 879 non‐BCSDs (6.44%) and 28, 784 BCSDs (14.39%). The oldest age group (>62 years), black race, and a single or divorced marital status were associated with more non‐BCSDs. With adjustments for age, a hormone receptor–positive (HoR+) status was no longer related to increased non‐BCSDs. In patients with grade 1, stage I disease and an HoR+ status as well as the oldest subgroup, a great dilution of non‐BCSD on all causes of death could be observed, and this led to incorrect interpretations. The inaccuracy, caused by the commonly used Cox proportional hazards model, could be corrected by a competing risk model. CONCLUSIONS: OS was largely impaired by non‐BCSD during early breast cancer. For some future clinical trial planning, especially for the oldest patients and those with HoR+ breast cancer, non‐BCSD should be considered a competing risk event. Cancer 2017;123:2432–43. © 2017 American Cancer Society . Abstract : Overall survival is based on the absolute risk of death and does not take into account competing causes of death, which can be largely diluted by non–breast cancer–specific deaths during early breast cancer. For some future clinical trial planning, especially for old patients and patients with hormone receptor–positive breast cancer, non–breast cancer–specific death should be considered as a competing risk event.